Accelerated renal disease is associated with the development of metabolic syndrome in a glucolipotoxic mouse model - Cristina Martínez-García; Adriana Izquierdo; Vidya Velagapudi; Yurena Vivas; Ismael Velasco; Mark Campbell; Keith Burling; Fernando Cava; Manuel Ros; Matej Orešič; Antonio Vidal-Puig; Gema Medina-Gomez (The Company of Biologists, 2012)
SUMMARY Individuals with metabolic syndrome are at high risk of developing chronic kidney disease (CKD) through unclear pathogenic mechanisms. Obesity and diabetes are known to induce glucolipotoxic effects in metabolically relevant organs. However, the pathogenic role of glucolipotoxicity in the aetiology of diabetic nephropathy is debated. We generated a murine model, the POKO mouse, obtained by crossing the peroxisome proliferator-activated receptor gamma 2 (PPARγ2) knockout (KO) mouse into a genetically obese ob/ob background. We have previously shown that the POKO mice showed: hyperphagia, insulin resistance, hyperglycaemia and dyslipidaemia as early as 4 weeks of age, and developed a complete loss of normal β-cell function by 16 weeks of age. Metabolic phenotyping of the POKO model has led to investigation of the structural and functional changes in the kidney and changes in blood pressure in these mice. Here we demonstrate that the POKO mouse is a model of renal disease that is accelerated by high levels of glucose and lipid accumulation. Similar to ob/ob mice, at 4 weeks of age these animals exhibited an increased urinary albumin:creatinine ratio and significantly increased blood pressure, but in contrast showed a significant increase in the renal hypertrophy index and an associated increase in p27Kip1 expression compared with their obese littermates. Moreover, at 4 weeks of age POKO mice showed insulin resistance, an alteration of lipid metabolism and glomeruli damage associated with increased transforming growth factor beta (TGFβ) and parathyroid hormone-related protein (PTHrP) expression. At this age, levels of proinflammatory molecules, such as monocyte chemoattractant protein-1 (MCP-1), and fibrotic factors were also increased at the glomerular level compared with levels in ob/ob mice. At 12 weeks of age, renal damage was fully established. These data suggest an accelerated lesion through glucolipotoxic effects in the renal pathogenesis in POKO mice.